Early Detection of High Risk Pregnancy - Kurniawan, Arif; Sistiarani, Colti; Hariyadi, Bambang (Jurnal Kesehatan Masyarakat, 2017)
There are 30.939 pregnant women in Banyumas, with 6.206 cases referred due to high-risk pregnancies. Petahunan village in Pekuncen has the the highest incidence of high-risk pregnancies compared with other villages. The purpose of this study is to describe the implementation of early detection of high-risk pregnancies in Petahunan village, Pekuncen. This study used qualitative research methods with case study approach. Research instruments used in-depth interviews and focus group disscussion toward early detection of high-risk pregnancy issue. The informants were 7 people include pregnant women, health workers, midwives, head of village and village health forum chairman. The result showed only antenatal care implemented to detect high-risk pregnancy and no programs and community empowerment efforts in early detection of high-risk pregnancies.